Upholding Fundamental Rights in National Arrest Warrant Proceedings in Practice: a Need for Third Level of Judicial Protection? - Tralmaka, Ilze (European journal on criminal policy and research, 2022)
The European Commission has repeatedly attempted to introduce EU legislation on pre-trial detention but has so far met with an overwhelming reluctance of Member States to address the issue. The latest initiative proposes to adopt an EU recommendation on the rights and conditions in pre-trial detention. This article seeks to highlight gaps in the protection of fundamental rights in national arrest warrant proceedings and whether standards on pre-trial detention alone will offer a solution for the full protection of fundamental rights in a cross-border context. It draws the link between the national arrest warrant, the EAW and the responsibility of the issuing state to guarantee the legality and validity of the national arrest warrant. The article finds that currently, compliance of judicial decision-making with the existing ECHR standards on pre-trial detention cannot be presumed in practice. This compliance also cannot be verified in an adversarial and equal judicial process until after the requested person has been surrendered. In the absence of a judicial process to challenge the legality of a national arrest warrant before the execution of an EAW, protection of the requested person’s rights and access to an effective remedy remains problematic.